Scanning electron microscopy of leaves in the West African polygonaceae (2008)
The leaf surfaces of the West African taxa of the Polygonaceae were studied using the Scanning Electron Microscope (SEM). Leaf epidermal cells arc polygonal, isodiametric and rarely irregular. Anticlinal walls are straight, curved, undulate or sinuate. Striae are present in a few taxa such as Polygonum plebeium. Rumex abysinaicus, R. bequaertii, Oxygonum sinuatum, Persicaria nepalensis and Afrobrunnichia erecta. The striae may be parallel, radiate, or randomly distributed. Trichomas are unicellular, uniseriate, aggregating together in some species of persicaria, while they may be flagelliform, interwoven and woolly in Persicaria senegalensis forma albotomentosa hence diagnostic for the species. Peltate glands are characteristic of A. arena. Stomata are mainly paracytic or anomocytic although diacytic. cyclocytic and anisocytic types may also be found in some taxa sometimes together with the main types. Stoma’s are sunken in a few species such as Polygonum plebeium and Persicaria attenuata subsp. pulchra, raised or at the same level with epidermal cells in other taxa. Wax deposits arc associated with the stomata in Persicaria attenuata subsp. africana. These characters are discussed in relation to the taxonomy of the family in West Africa.